NOTES ON THE START DATE OF THE POIENEȘTI-LUCAȘEUCA CULTURE - Vasile Iarmulschi (Journal of Ancient History and Archaeology)
In this study, we analyse the issue of the start date of the Poienești-Lucașeuca culture. Based on the dating of certain categories of items discovered in both funerary and habitation sites but also on the information supplied by certain written sources we set the chronological limit of this culture to the last quarter of the 3rd century BC.